Dapatkah Otak yang Rusak Bertanggung Jawab? Disrupsi Amigdala–PFC dan Rekonstruksi Moralitas dalam Hukum Pidana - Zul Khaidir Kadir (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Criminal liability in modern law is built on the assumption that every individual is a rational and autonomous moral agent. However, neuroscientific evidence suggests that structural disruption of the amygdala and prefrontal cortex significantly impairs the capacity to judge actions ethically. This study aims to analyze the influence of neurological disorders on an individual's moral capacity and to formulate legal parameters for assessing criminal liability based on actual capacity. The research method employed normative legal research with a conceptual approach. The results indicate that perpetrators with dysfunction in the amygdala-PFC circuit experience a degradation of moral capacity that weakens the basis for the formation of mens rea in a substantive sense and falls outside the reach of legal systems that still rely on a model of responsibility based on the assumption of universal free will. The criminal legal system, in its current form, lacks a precise evaluative mechanism to distinguish between perpetrators with impaired moral control and those acting deliberatively. In this situation, the construction of criminal liability cannot be standardized, and reformulation of evaluation instruments is necessary to avoid sentencing bias against individuals with structural impairments in ethical capacity.